The Prevalence of Complementary and Alternative Medications Use Among Dermatology Patients in Aseer Region, Saudi Arabia - Al-Atif HM; AL-Ghamdi HS; Alzubaidi WA; Alnaem NM; Qahtani SH (Dove Medical Press, 2022)
Hend M Al-Atif,1 Hasan S AL-Ghamdi,2 Waad Abdulaziz Alzubaidi,3 Nejad Mubasher Alnaem,3 Saad Hussain Qahtani3 1Department of Internal Medicine, College of Medicine, King Khalid University, Abha City, Kingdom of Saudi Arabia; 2Internal Medicine Department, Division of Dermatology, Faculty of medicine, Albaha University, Albaha City, Kingdom of Saudi Arabia; 3College of Medicine, King Khalid University, Abha City, Kingdom of Saudi ArabiaCorrespondence: Hend M Al-Atif, Tel +966556464612, Email hotaif@kku.edu.saPurpose: The utilization rate of complementary and alternative medication (CAM) is on the rise, especially for the general population. Despite the lack of scientific support, CAM has been used for decades and is more often used among chronic patients. This research examines the prevalence of CAM use in dermatology patients in the area of Aseer, Saudi Arabia.Materials and Methods: This research was done using a descriptive hospital-based cross-sectional survey among adults who attended the dermatological clinics at the major hospitals in the Aseer area of Southern Saudi Arabia. The dermatology outpatients were approached individually and were asked to fill out a survey about their usage of CAM therapies in the preceding year. The questionnaire included questions on patients' socio-demographic data and clinical data on their dermatological condition, including duration and the effect on their daily life. The occurrence and pattern of CAM use and the type of CAM utilized were also examined.Results: 353 dermatological patients filled out the study questionnaire. Patients varied in age from 18 to above 60 years, with an average of 26.1 ± 12.9 years. 203 (57.5%) patients were females. 120 (34%) of the study patients reported using folk medicine with doctor medication for their dermatological disorder, 84 (23.8%) used folk medicine and stopped using medications prescribed by a doctor, while 149 (42.2%) never used folk medicine. The most used CAM was olive oil (22%), followed by sidr (21%), honey (19%), cactus (15%), henna (14%), and garlic (13%).Conclusion: More than half of the participants in this study used CAM, with nearly 1 out of 5 patients not using the medications prescribed by their physicians. Females with long-lasting diseases were the main users who reported using a variety of CAMs. Satisfactory results were experienced by nearly half of the patients.Keywords: complementary or alternative medications, dermatology, use, prevalence, knowledge, effect, Saudi Arabia